2014
DOI: 10.1016/j.nutres.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Intake of milk, but not total dairy, yogurt, or cheese, is negatively associated with the clustering of cardiometabolic risk factors in adolescents

Abstract: Epidemiologic studies have reported an inverse association between dairy product consumption and cardiometabolic risk factors in adults, but this relation is relatively unexplored in adolescents. We hypothesized that a higher dairy product intake is associated with lower cardiometabolic risk factor clustering in adolescents. To test this hypothesis, a cross-sectional study was conducted with 494 adolescents aged 15 to 18 years from the Azorean Archipelago, Portugal. We measured fasting glucose, insulin, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 62 publications
2
39
0
2
Order By: Relevance
“…The most studied comparisons include raw with processed fruits and vegetables (34,35), whole-grain with refined cereals (36)(37)(38), red with processed meats (39,40), milk with yogurt with cheese (41,42), and full-fat versus semiskimmed with low-fat/skimmed milk (or low-fat compared with high-fat dairy) (43,44). For example, raw and processed fruit and vegetable products have been shown to protect against coronary heart disease risk, whereas only raw products protected against stroke (34,35).…”
Section: Association Between Usual Food Groups and Chronic Disease Rimentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied comparisons include raw with processed fruits and vegetables (34,35), whole-grain with refined cereals (36)(37)(38), red with processed meats (39,40), milk with yogurt with cheese (41,42), and full-fat versus semiskimmed with low-fat/skimmed milk (or low-fat compared with high-fat dairy) (43,44). For example, raw and processed fruit and vegetable products have been shown to protect against coronary heart disease risk, whereas only raw products protected against stroke (34,35).…”
Section: Association Between Usual Food Groups and Chronic Disease Rimentioning
confidence: 99%
“…Red and processed meats have been consistently positively associated with an increased risk of colon adenoma (39) and colorectal cancer (40). Results regarding dairy products have depended on the products and diseases considered with mixed effects; milk and yogurt have been shown to protect against cardiovascular risk, whereas no association was observed for cheese (41,42). Moreover, no association was reported between cheese and whole-milk intake and prostate cancer risk, whereas skimmed/low-fat milk has been shown to slightly increase risk (43).…”
Section: Association Between Usual Food Groups and Chronic Disease Rimentioning
confidence: 99%
“…However, investigations in this field have yielded contradictory results [5-7]. In this context, there are some studies that have reported an association between MetS and dairy products as a whole [7-9], and some that described the independent effect of various dairy products (especially milk, yogurt and cheese) [6,10]. Concerning results on yogurt consumption, the conclusions obtained are all in the same direction suggesting a significant inverse association between yogurt consumption and the development of MetS [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among recent cross-sectional studies, sixteen found an inverse relationship between dairy consumption and adverse metabolic outcomes (positive findings), (34; 47; 48; 49; 50; 51; 52; 53; 54; 55; 56; 57; 5 8; 59; 60; 61; 62) while five had mixed findings (71; 74; 75; 76; 77; 78) and the remaining studies failed to detect an association in the expected direction. (79; 80; 81) Among positive findings, a study of 827 Iranian adults (18–74y) concluded that the uppermost quartile of dairy consumption (vs. lowest) had reduced odds of central obesity, hypertension and MetS, an association primarily mediated by calcium intake, (34) as was replicated in a separate study.…”
Section: Discussionmentioning
confidence: 99%
“…(23) Recent observational and experimental studies suggest that dairy and calcium consumption may reduce obesity risk, (29; 30) excess central (31) fat distribution, type-2 diabetes (32; 33) , hypertension (34) , and the MetS (31; 34; 35; 36; 37; 38; 39; 40; 41; 42; 43; 44; 45; 46; 47; 48; 49; 50; 51; 52; 53; 54; 55; 56; 57; 58; 59; 60; 61; 62; 63; 64; 65; 66; 67; 68) , while mixed or negative finding were reported by others. (69; 70; 71; 72; 73; 74; 75; 76; 77; 78; 79; 80; 81; 82; 83) …”
Section: Introductionmentioning
confidence: 99%